2022
DOI: 10.18817/26755122.26.01.2022.2899
|View full text |Cite
|
Sign up to set email alerts
|

Regionais De Saúde E Os Casos De Dengue No Mato Grosso: A Chuva Como Principal Fator Para a Proliferação Do Aedes Aegypti

Abstract: Esta pesquisa caracterizou espacialmente e temporalmente (2001 a 2019) a dinâmica da dengue no estado de Mato Grosso. Estudo epidemiológico e descritivo da taxa de incidência e da mortalidade por dengue, procurando correlacionar com pluviosidade, Índice de Desenvolvimento Humano (IDH), Densidade Demográfica e o Índice de Sustentabilidade de Limpeza Urbana (ISLU). A incidência de dengue não apresentou relação significativa com o (ISLU) em 66 municípios do estado de Mato Grosso (R²=0,0017; p=0,75). Isso também o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This analysis was based on data from the Urban Cleaning Sustainability Index (2019), which showed that environmental waste was correctly disposed of in only 18.64% of the region, a lower percentage than in other areas in Brazil. (11) Regarding the symptoms of severe dengue a retrospective cohort study of a reference pediatric hospital in the city of Rio de Janeiro, found that 30.4% of the patients had dyspnea. These data corroborate the results of the present study, in which 29.5% of patients presented with respiratory failure resulting from the accumulation of fluids in the third space.…”
Section: ❚ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was based on data from the Urban Cleaning Sustainability Index (2019), which showed that environmental waste was correctly disposed of in only 18.64% of the region, a lower percentage than in other areas in Brazil. (11) Regarding the symptoms of severe dengue a retrospective cohort study of a reference pediatric hospital in the city of Rio de Janeiro, found that 30.4% of the patients had dyspnea. These data corroborate the results of the present study, in which 29.5% of patients presented with respiratory failure resulting from the accumulation of fluids in the third space.…”
Section: ❚ Resultsmentioning
confidence: 99%
“…It is likely that this occurs because this area has a high population concentration with different social conditions, accelerated and uncontrolled growth, without adequate infrastructure for the speed of urban development, and because they are constantly receiving immigrants, which facilitates the proliferation and dissemination of the vector. ( 2 , 11 ) An article published in Ciência Geográfica states that one possible explanation for the prevalence of dengue in the Midwest region is related to urban cleanliness. This analysis was based on data from the Urban Cleaning Sustainability Index (2019), which showed that environmental waste was correctly disposed of in only 18.64% of the region, a lower percentage than in other areas in Brazil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A taxa do metabolismo do vetor tem um aumento nos meses mais quentes, fazendo com que seu ciclo seja abreviado em até oito dias, enquanto que em baixas temperaturas isso acontece em vinte e dois dias. (15,16) Exatamente nos meses de janeiro a abril de 2021 é possível perceber o aumento dos casos.…”
Section: Resultados E Discussõesunclassified